AJCC 8th edition pathologic nodal staging of resected pancreatic adenocarcinoma predicts survival regardless of treatment sequencing. (March 2022) - Oppliger, Federico A.; Prakash, Laura R.; Newhook, Timothy E.; Chiang, Yi-Ju; Ikoma, Naruhiko; Maxwell, Jessica E.; Kim, Michael P.; Vauthey, Jean-Nicolas; Lee, Jeffrey E.; Katz, Matthew H.; Tzeng, Ching-Wei D.
Abstract: Objective: The primary aim was to compare overall survival (OS) between neoadjuvant therapy (NT) and surgery-first (SF) patients with pancreatic adenocarcinoma (PDAC) by nodal stage using the American Joint Commission on Cancer 8th Edition (AJCC8). Background: Rates of nodal positivity are consistently lower following NT versus SF sequencing. It's unclear whether post-NT nodal stage (ypNx) has similar survival compared to SF (pNx) using AJCC8. Methods: This is a single-institution retrospective cohort study with routine consideration of NT. Patients undergoing PDAC resection from 2010 to 2018 were analyzed and OS compared by nodal stage using AJCC8. Results: Of 450 total patients, 24% were treated with SF and 76% NT. SF patients had potentially resectable disease in 97% of the cases, whereas NT patients had more advanced clinical stages at diagnosis: borderline resectable 34%, locally advanced 5%. NT patients had higher rates of node-negativity (52.4% vs 22.7%) and lower rates of pathologic N2 disease (19.1% vs 43.6%) vs. SF (p < 0.001). For each pathologic nodal stage, SF and NT groups had similar 5-year OS [pN0/ypN0 52.7% vs. 53.6%, p = 0.723], [pN1/ypN1 37.0% vs. 36.7%, p = 0.872], and [pN2/ypN2 16.6% vs. 21.0%, p = 0.508]. Conclusions: AJCC8 stratifies outcomes for each post-NT nodal stage similar to SF counterparts. Despite presenting with more advanced clinical stage, NT patients had lower rates of nodal metastases yet comparable OS when stratified by final nodal status. These data provide both hope for patients with obvious radiographic nodal disease at presentation and further support for considering NT sequencing for most patients diagnosed with localized PDAC. Highlights: Surgery upfront versus neoadjuvant by nodal staging for pancreatic adenocarcinoma. Pathologic nodal staging associated with overall survival. Validates the AJCC 8th nodal staging system after neoadjuvant therapy. Patients who received neoadjuvant therapy had lower rates of nodal metastases. Comparable survival despite neoadjuvant group with more advanced pre-treatment disease.